Performance Evaluation of Integrated Antennas on Photovoltaic Solar Cells - Ahmed Al-Alawi; Said Al Gheilani; Ahmed Al-Zeidi; Mohammed Bait-Suwailam (Engineering and Technology Journal, 2023)
The performance of antennas is critical to ensuring reliable wireless communication and robust data transmission. Unfortunately, antennas’ performance gets degraded when loaded with lossy materials. This paper presents the numerical and experimental evaluation of low-profile antennas’ performance when integrated with photovoltaic (PV) solar cells for potential use in smart grid and green power networks. Such integrated antennas can serve as a communication unit and sensors to monitor PV solar cells. For convenience, a microstrip patch antenna was used in this assessment study, where the antenna was designed, numerically simulated, and experimentally tested. After which, it was installed on top of a PV solar cell at different orientations. The antenna is designed to operate within the 2.45 GHz ISM band. Based on the results, the antenna performed well when placed at the middle of the PV solar cell with a peak gain of 2.58 dBi compared to other placements within the PV solar cell. Moreover, creating a small air gap between the antenna and the PV solar cell results in better performance. Based on the findings of this study, the antenna has satisfactory performance when integrated with PV cells, which is promising to deploy in many applications, including smart grid networks.